Increasing Employee Job Satisfaction Through Spiritual Leadership and Islamic Organizational Culture: Meningkatkan Kepuasan Kerja Karyawan Melalui Kepemimpinan Spritual dan Budaya Organisasi Islami - Eka Mariyanti; Riri Putri; Nica Susanti (International Journal of Management and Business (IJMB), 2020)
The development of sharia-based hotels has become a popular business and it is believed that the development of sharia hotels will experience a drastic increase due to the level of business awareness of sharia concepts. This study aims to improve employee job satisfaction through spiritual leadership and Islamic organizational culture. This study uses a descriptive qualitative approach. The unit of analysis is employees who work at Sharia Hotels in Padang. The results showed that partially Spiritual Leadership variables had a positive and significant effect on Job Satisfaction and Islamic Organizational Culture variables had a positive and significant effect on Job Satisfaction variables. Simultaneously the Spiritual Leadership and Islamic Organizational Culture has a positive and significant effect on Employee Job Satisfaction with an adjusted R2 value of 0.204 This shows that the magnitude of the influence of the Islamic Organizational Spiritual Leadership and Culture on the variable Job satisfaction is 20.4%.